Thymoquinone induces apoptosis and increase ROS in ovarian cancer cell line - Taha, M M E; Sheikh, B Y; Salim, L Z A; Mohan, S; Khan, A; Kamalidehghan, B; Ahmadipour, F; Abdelwahab, S I (Cellular and Molecular Biology, 2016)
Nigella sativa is also known for its properties as a traditional herbal healing for many ailments. In this study, the anticancer properties of thyomquinone (TQ), the active ingredient of N. sativa, were studied using ovarian cancer cell line (Caov-3 cells). The anti-proliferative activity of TQ was determined using MTT and the apoptosis was investigated using Flowcytometry and Annexin-V Assays. Multiparameteric cytotoxicity bioassays were used to quantify the changes in cell permeability and mitochondrial membrane potential. Reactive oxygen species (ROS) and apoptosis-involved cell markers were examined to verify cell death mechanism. The MTT-assay showed that TQ induces anti-proliferative activity on Caov-3 with an IC50 of 6.0±0.03 Î¼g/mL, without any cytotoxic activity towards WRL-68 normal hepatocytes. A significant induction of early phase of apoptosis was shown by annexin-V analysis. Treatment of Caov-3 cells with TQ induces decreases in plasma membrane permeability and mitochondrial membrane potential. Visible decrease in the nuclear area was also observed. A significant decrease is observed in Bcl-2 while Bax is down-regulated. TQ-triggered ROS-mediated has found to be associated with Hsp70 dysregulation, an indicator of oxidative injury. We found that TQ induced anti-cancer effect involves intrinsic pathway of apoptosis and cellular oxidative stress. Our results considered collectively indicated that thyomquinone may be a potential agent for ovarian cancer drug development.